Compact Multiband Microstrip Printed Slot Antenna Design for Wireless Communication Applications - Hammas, H. A.; Hasan, M. F.; Jalal, A. S. A. (Advanced Electromagnetics, 2020)
In this paper, a compact multiband printed antenna is proposed to cover four resonant bands in the range of 1-6 GHz. The antenna structure is inspired from that of the classical multi-cavity magnetron resonator. The antenna comprises a slot annular ring structure in the ground plane of an Isola FR4 substrate having Ԑr = 3.5 and thickness h=1.5 mm. The outer circle of the annular ring is loaded with radial arranged small circular slots. On the opposite side of the substrate, the antenna is fed with a 50-Ohm microstrip line. To investigate the effect of different antenna elements on the antenna performance, a parametric study is conducted. The antenna is simulated, fabricated, and measured. The simulated 10 dB return loss bandwidths for the four resonant bands are 35% (1.53–2.11GHz), 14% (2.9–3.34GHz), 12% (4.2–4.75GHz), and 9% (4.94–5.39GHz), respectively. Thus, the antenna is a proper candidate for many in use bands of wireless systems (1.65, 3.14, 4.44, 5.24 GHz), including LTE-FDD, GNSS, GSM-450, W-CDMA/HSPA/k, 802.11a, and IEEE 802.11ac WLAN. The results indicate that the designed antenna has quad-band resonant responses with substantial frequency ratios of f4/f3, f3/f2 and f2/f1. Besides, the antenna offers reasonable radiation characteristics with a gain of 2.5, 4.0, 6.2, and 4.2 dBi, throughout the four resonant bands.